A novel investigation study on float glass hole surface integrity & tool wear using Chemical assisted Rotary ultrasonic machining. (2020) - Sharma, Ankit; Jain, Vivek; Gupta, Dheeraj
Abstract: To alleviate the alarming surface integrity defect (chipping) and tool wear issues, new machining technique has been introduced. First time, an attempt has been made by hybrid the 'Rotary ultrasonic machining' and 'Chemical etching process' that pioneer as 'Chemical assisted Rotary ultrasonic machining'. In this work, authors have investigated a novel study to explore the float glass's drilled hole surface integrity and tool wear. The mechanism behind the hole surface integrity and tool wear is also discussed. The results pointed that the Chemical assisted Rotary ultrasonic machining (CRUM) gives slightest chipping size (0.32 mm) using abrasive coated hollow tool of 6 mm diameter over the 5% HF acid dipped float glass specimen. However, coz of highly chemical reacting behaviour of HF acid with the tool material, it is deteriorated. Thus more research needed to be carried for the tool selection. Finally, authors recommended that the Chemical assisted Rotary ultrasonic machining is having a vibrant future.